Maximizing Energy Transference in PMSG with Arbitrary EMF Waveform - Catuogno, Guillermo Ricardo (2014)
A control method is proposed with the objective of maximizing the energy transference in permanent magnet synchronous generators (PMSG). Such control is based on the evaluation of instantaneous power components. First, the conventional control strategy 6 steps for PMSG in compared with the strategy proposed for 3-wire systems where the latter has the advantage of minimizes copper losses and reduce torque ripple. Then a 4-wire systems is analyzed, the topology implemented connect the neutral point of the generator to the midpoint of the DC bus capacitor bank, in these case, the strategy proposed can increase the energy transfer exploiting the homopolar current flow. Simulation results are presented and analyzed to validate the proposed strategies for generators with three different EMF waveforms. From these results, it can be concluded that when neutral is connected, it is possible to take advantage of the homopolar components of the generator EMF by imposing and adequate current with the objective of maximizing the generator power.